2012
DOI: 10.1530/joe-12-0077
|View full text |Cite
|
Sign up to set email alerts
|

Local overexpression of GH and GH/IGF1 effects in the adult mouse hippocampus

Abstract: GH therapy improves hippocampal functions mainly via circulating IGF1. However, the roles of local GH and IGF1 expression are not well understood. We investigated whether transgenic (TG) overexpression in the adult brain of bovine GH (bGH) under the control of the glial fibrillary acidic protein (GFAP) promoter affected cellular proliferation and the expression of transcripts known to be induced by systemic GH in the hippocampus. Cellular proliferation was examined by 5-bromo-2 0 -deoxyuridine immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…In our previous studies, we have shown that Hbb is robustly regulated by GH in female rats (Walser et al 2012). Although endogenous neuronal (non-erythrocyte) hemoglobin has been found in neurons of rodents and human brain, its function is still not fully clear (Richter et al 2009, He et al 2010.…”
Section: Effects Of Gh Administration With Respect To Plasticity and mentioning
confidence: 96%
“…In our previous studies, we have shown that Hbb is robustly regulated by GH in female rats (Walser et al 2012). Although endogenous neuronal (non-erythrocyte) hemoglobin has been found in neurons of rodents and human brain, its function is still not fully clear (Richter et al 2009, He et al 2010.…”
Section: Effects Of Gh Administration With Respect To Plasticity and mentioning
confidence: 96%
“…Exercise increases the uptake of IGF-1 [35] from the bloodstream into various brain regions. Although the detailed mechanisms of the reduced brain degeneration remain unclear, it may be related to the attenuation of aging-related neuronal death [36] and the jump-start of hippocampus neuron proliferation [37]. (2) It is worth mentioning that not all intensity-associated stress levels show the same effects on neuroplasticity.…”
Section: Discussionmentioning
confidence: 99%
“…25 However overexpression of GH in mouse hippocampus is associated with only a modest change in local IGF-I expression. 26…”
Section: Igf System Overviewmentioning
confidence: 99%
“…25 However overexpression of GH in mouse hippocampus is associated with only a modest change in local IGF-I expression. 26 Insulin-like growth factor inhibits GH secretion through endocrine negative feedback, crossing the fenestrated sinusoid capillaries of the anterior pituitary, and inhibiting spontaneous and GHRH-stimulated GH release by somatotrophs. 16 It is also possible that there is negative feedback by IGF-I on GHRH in the hypothalamus.…”
mentioning
confidence: 99%